2012
DOI: 10.21608/eajbsa.2012.14792
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic (Gentamicin) Impact on Bacterial Flacherrie Disease of Silkworm, Bombyx mori L..

Abstract: There are many factors that influence the success of silk production. Bacterial flacherrie considered the most important factor. Antibiotics showed promising results for controlling of silkworm diseases and to improve the production of silk and harvesting superior crop. The effect of antibiotic (Gentamicin) upon the infection with bacterial flacherrie was discussed. Gentamicin as a cheap antibiotic in Egypt can be used easily by trainees and farmers. It was found that Gentamicin significantly increases the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…It was found that ciprofloxacin significantly increases the effective rate of rearing and cocoon weights and cocoon length and width were significantly increased under the effects of antibiotic treatment comparing with control. Similar effect by gentamycin was reported by Mahmoud et al (2012). Use of antibiotic to prevent bacterial disease of silkworm has also been reported by many studies (Hamamoto et al 2005, Kaito et al 2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was found that ciprofloxacin significantly increases the effective rate of rearing and cocoon weights and cocoon length and width were significantly increased under the effects of antibiotic treatment comparing with control. Similar effect by gentamycin was reported by Mahmoud et al (2012). Use of antibiotic to prevent bacterial disease of silkworm has also been reported by many studies (Hamamoto et al 2005, Kaito et al 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Antibiotics are used to find out their effectiveness against pathogenic bacteria (Mahmoud et al 2012). As a result, bacteria associated with silkworm are prone to develop resistance to commonly used antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Impact of different antibiotics on the development and cocoon production of silkworm has been evaluated and established in some studies (Javaid et al, 2021;Rafiq et al, 2021b). Antibiotic administration significantly enhanced the biological and commercial traits of silkworm (Rahmathulla et al, 2003;Hamamoto et al, 2004b;Adel et al, 2015;Shyamala et al, 2013;Savithri, 2007;Rahmathulla and Nayak, 2017;Kushelaf et al, 2014;Mahdi et al, 2017b;Mahmoud and Taha, 2012). In our study, three concentrations of each levofloxacin and cefixime showed significant effects on larval growth, cocoon production, and bacteria associated with silkworms.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial disease management in silkworms has been achieved by exposing larvae to different antibiotics with encouraging results (Hamamoto et al, 2004a;Javaid et al, 2021;Rafiq et al, 2021a). Antibiotics are used in the sericulture industry as an element of bed sterilizers and therapeutic impact in bacterial diseases management (Venkatesh and Srivastava, 2010;Srivastava and Kumar, 2009;Mahmoud and Taha, 2012;Subramanian et al, 2010). Such antibiotics include penicillin, ampicillin, tetracycline, erythromycin, and chloramphenicol that showed promising results in bacterial disease management of silkworm larvae Subramanian et al, 2010;Venkatesh and Srivastava, 2010;Ashok and Ramakrishna, 2014;Prakash and Puttaraju, 2006;Kaito et al, 2011;Kaito and Sekimizu, 2007;Meng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tetracycline (30 µg/mL), Amoxicillin (25 µg/mL), Ampicillin (10 µg/mL), Erythromycin (15 µg/mL) and Penicillin (10 µg/mL) were used in the study. The mulberry leaves dipped in the antibiotic solutions were fed during the 4 th and 5 th instar larvae (Mahmoud et al, 2012). The silkworm larvae were fed on antibiotic-treated mulberry leaves during the 4 th and 5 th instars at an interval of 12 hrs.…”
Section: Antibiotic Treatmentmentioning
confidence: 99%